2014
DOI: 10.1158/1535-7163.mct-13-0575-t
|View full text |Cite
|
Sign up to set email alerts
|

PIM Kinases Are Essential for Chronic Lymphocytic Leukemia Cell Survival (PIM2/3) and CXCR4-Mediated Microenvironmental Interactions (PIM1)

Abstract: Overexpression of the CXCR4 receptor is a hallmark of chronic lymphocytic leukemia (CLL) and is important for CLL cell survival, migration, and interaction with their protective microenvironment. In acute myelogenous leukemia (AML), PIM1 was shown to regulate the surface expression of the CXCR4 receptor. Here, we show that PIM (proviral integration site for Moloney murine leukemia virus) kinases 1-3 are overexpressed and that the CXCR4 receptor is hyperphosphorylated on Ser339 in CLL compared with normal lymph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 55 publications
5
85
0
6
Order By: Relevance
“…Pim-1 overexpression has been associated with upregulated cell surface expression of CXCR4 in hematopoietic malignancies such as acute myeloid leukemia [4], diffuse large B-cell lymphoma [28] and chronic lymphocytic leukemia [29]. The intracellular tail of CXCR4 can be phosphorylated in vitro at Ser339 by Pim-1 kinase [4] and by Pim-3, as shown here, but not by Pim-2.…”
Section: Discussionmentioning
confidence: 65%
“…Pim-1 overexpression has been associated with upregulated cell surface expression of CXCR4 in hematopoietic malignancies such as acute myeloid leukemia [4], diffuse large B-cell lymphoma [28] and chronic lymphocytic leukemia [29]. The intracellular tail of CXCR4 can be phosphorylated in vitro at Ser339 by Pim-1 kinase [4] and by Pim-3, as shown here, but not by Pim-2.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, several studies have demonstrated that CXCR4-serine 339 phosphorylation is crucial for tumour cell migration and metastasis121718. Although CXCR4-serine 339 phosphorylation should mainly be observed upon activation of the ligand SDF-1, it cannot include all situations.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, there is increasing evidence showing that CXCR4-serine 339 phosphorylation is important in solid cancer cells for regulating cellular adhesion, retention and mobilization171824, and it has also been reported that CXCR4-serine 339 is significantly associated with poor overall survival in B-cell acute lymphoblastic leukaemia17. Thus, CXCR4-serine 339 phosphorylation may not only be a concomitant phenomenon in the presence of SCF stimulation but may also play an important role in SCF-induced cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, genetic knock-down of Pim-1 has also been shown to decrease the expression of ABCB [59], confirming the critical role of Pim-1 in drug resistance. More physiological implications of Pim kinase in senescence, migration and metabolism have also been discussed in many studies [44,56,[61][62][63][64][65]. Taken together, Pim-1 affects the multiple key components of signaling pathways that are essential to survival and proliferation of cancer cells.…”
Section: P Im1 Y Q V G P L L G S G G F G S V Y S G I R V S D N L P V mentioning
confidence: 94%